Thoughts of body-space awareness through dance for pre-school children - Maskens, Francis (Taideyliopiston Teatterikorkeakoulu, 2026)
As I look back on my own education, I have come to the realisation of how dance has supported my growth and development as a human being and later as an artist and educator. I hope there can be a world where all children are met and supported in a way that best suits their needs within their education and learning. My question within the thesis is: how can dance support pre-school children’s development in their education. The thesis speaks about how we can teach children, how dance can support relationship with oneself, space and one another. My aim is to better understand how dance could be of benefit to preschool children’s development of body-space awareness. More specifically my purpose in this inquiry was to find ways dance could support motor skill and creative development in preschool children. The inquiry was done in collaboration with Duckies bilingual daycare in Helsinki, where I facilitated five dance classes in the spring of 2024. My thesis describes a practical section of the inquiry. This query uses qualitative research method of participant observation to inquire and log how dance could support pre-school children’s interactions with space and body. I collected the data in the format of voice recordings, that I made after each session to reflect my observations. Through my thesis I noticed that especially dance exploration can be a way of supporting the teacher and students work, through its spontaneous and multi-layered ways of connecting with self, each other and space. The child as a learner, in my thoughts within this thesis, is a person to be fostered and supported. But also, someone to learn from. We are in a sense all children and dance a canvas for bodily exploration and consciousness of relation between ourselves and the world’s complexities. The field of dance pedagogy is supported by this work through its questions. The observation of children’s embodied learning and connection with the world through dance, allows us as pedagogues to better understand how learning through the body can occur. Children’s reactions to movement explorational tasks allow to understand how we as educators can best support curiosity and engagement. Dance pedagogical research and working with children supports discussion on how dance can be meaningful, educational support from the very start of education.
Keywords: tanssi; opetus; tanssinopettajat; tanssikasvatus; taidekasvatus; lapset (ikäryhmät); pedagogiikka; varhaiskasvatus; tanssiteokset; vuorovaikutus; esikouluikäiset; fi=tanssinopettaja|sv=danspedagogik|en=Dance Pedagogy|